Engineering Tumour Cell-Binding Synthetic Polymers with Sensing Dense Transporters Associated with Aberrant Glutamine Metabolism - Yamada, Naoki; Honda, Yuto; Takemoto, Hiroyasu; Nomoto, Takahiro; Matsui, Makoto; Tomoda, Keishiro; Konno, Masamitsu; Ishii, Hideshi; Mori, Masaki; Nishiyama, Nobuhiro (Scientific reports, 2017)
Increased glutamine uptake toward the elevated glutaminolysis is one of the hallmarks of tumour cells. This aberrant glutamine metabolism has recently attracted considerable attention as a diagnostic and therapeutic target. Herein, we developed glutamine-functionalized polymer to achieve a selective high affinity to tumour cells overexpressing glutaminolysis-related transporter ASCT2. In in vitro study, our developed polymer exhibited faster and higher cellular uptake in tumour cells than that in normal cells. Uptake inhibition study revealed the dominant contribution of ASCT2 to the polymer-cell interaction. Furthermore, the binding affinity of the polymer to tumour cells was estimated to be comparable to that of the potent ligand molecules reported in the literature. In in vivo study, the polymer showed prolonged retention at tumour site after intratumoral injection. This study offers a novel approach for designing tumour cell-binding synthetic polymers through the recognition of dense transporters related to tumour-associated metabolism.